Kajian Penggunaan Bahasa Masyarakat Kedayan di Limbang, Sarawak - Nurul Syakinah, Wahed (Universiti Malaysia Sarawak (UNIMAS), 2021)
The Kedayan community is one of the indigenous minority tribes found intheBorneo archipelago at Sabah, the Federal Territory of Labuan, and Sarawak. Their main settlements in Sarawak can be found in Limbang, Lawas, Miri, Sibuti andBintulu. This study reports the results of the language choice of the Kedayancommunity in terms of domain and attitude of the speakers of the Kedayan communitytowards the Kedayan language. This study uses a quantitative data that is aquestionnaire method based on the theory Fishman’s (1972) domain to identify thelanguage choice of Kedayan community in terms of family, friendship, employment and religion domains. A total of 120 informants grouped based on three generations were selected based on quota sampling method. The results of the study found that theKedayan language is given priority in three domains such as family, friendship, andreligion for the first, middle and third generation. The Kedayan language was chosenbecause it is the mother tongue of the Kedayan community. As for the attitude of thespeakers, the researcher found that the attitude of the Kedayan community towards the Kedayan language is positive. The majority of respondents disagreed withthenegative attitudes that had been displayed. This has proved that there is a sense of pride in the Kedayan community when speaking in the Kedayan language